Functional-semantic interaction of concepts freedom, truth, strength in the discourse of the «Kobzar» (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
Intra- and intertekstuality interaction of lexical components freedom, truth , strength is considered as the precondition of formation of the phraseological unit. The role of adjectives as modifiers of conceptual semantics of designated nouns is investigated.
Keywords: phraseologication; the attributive structure; adjective; concept; ideologeme